النشاط الأشعاعي في الأغذية - افتخار حسن علوان; لازم خنيصر; اديبة ناجي; محمد خضير; زينب مطشر; انتصار فاضل; ميس علي; مها فاضل (Journal of Madenat Alelem University College, 2010)
Radioactivity was measured for about 405 samples of various imported foodstuffs and local communities through May 2007, 2008 and received by the health control at the Ministry of Health within the private sector imports, As well as through the Ministry of Agriculture through the purchase of food from local markets within the decision of the Advisory Body on Food campaign to control food, in addition to the ration card items. The samples included models (milk and milk products, red meat and Alda, beans, flour, cereals, oils, soft drinks, juices, tea, sugar and other materials. A"3 * 3" sodium iodide Scintillation detector with multichannel analyzer (MCA) was used to measure the activity of samples. The energy calibration was performed using a set of standard gamma – ray calibration sources Eu-152 . The results show the presence of radioactivity due to K-40 isotope in all samples of food. In addition it was noted also the presence of low due to Ra-226 isotope, in raw milk samples, and no fumbles device-to-peer Cesium -137 Was calculated radiation doses resulting from eating food imported and domestic as they hit the annual radiation dose of the Iraqi people (0.3) mSv / year is still within the allowable annual limit of exposure of members of the public recommended by the International Atomic Energy Agency, which amounts to (1 mSv / year ).